Factors Affecting Performance And Efficiency Of Rural Banks In Jakarta - Widyasari (International Journal of Economic Research and Financial Accounting, 2022)
This study aims to examine the influence of various factors that affect the performance and efficiency of Bank Perkreditan Rakyat (BPR). The analysis of this study is focused on the Bank Perkreditan Rakyat in Jakarta. Sample size was 72 firms-years during 2010-2012. The findings of this study show the influence of market forces, the intensity of bank loans, bank size, risk, quality of management and shareholder value simultaneously to the performance of BPR as follows for ROA was 67.51%, ROE of 64.96%, NII / TA amounted to 71.27%. Based on the results of the regression to examine the effect of market forces, the intensity of bank loans, bank size, risk, quality of management and shareholder value simultaneously to the efficiency of the bank amounted to 82.75% of BPR. Partially LNDEPO, LOANS_TA, NIE_TA negative and significant effect, and to influence LNTA positive and significant effect on efficiency, while for variable LLP_TL and EQUITY_TA not significant.